ENSINO E APRENDIZAGEM DE EQUAÇÕES DE DIFERENÇAS POR MEIO DA METODOLOGIA DE RESOLUÇÃO DE PROBLEMAS - Martin, Marivane de Souza (2011)
The present work´s aim was to analyze the contributions which the Teaching-Learning-Evaluation methodology through Problem Solving provides to the Equation of Differences concept learning, founded in the Concept Image and Concept Definition theory of Tall and Vinner (1981).The participants of the research were undergraduated students of the third grade of a Mathematics Teaching License, from UNIPAR Universidade Paranaense, Cascavel, PR. The research was a qualitative type and the collected dada was based on the participant observation during the development of the activities developed by the students in groups, registered in the researcher and the students ´ field diary and audio recording. The activities developed in the classroom followed the steps of Problem Solving method, suggested by Onuchic e Allevato (2009): problem preparation, individual reading of the problem, group reading, problem solving, observation and encouraging, solving record on the blackboard, plenary, search of agreement and formalization of the content. The activities developed in the classroom were organized in three learning units, aiming the concept building of Difference Equations. In the first unit problem-situations were studied involving problem situations which allowed the students to build the concept of Linear Equations of Differences of homogeneous first order; in the second unit problem situations involving Linear Equations of Differences of non-homogeneous first order and in the last unit problem situations were proposed related to Linear Equation of Differences of homogeneous of second order. The results indicated that in front of an unknown math concept, the students tried to mean it by means of their conceptual images which already exist and the new ones built during the research. It was possible to identify an active involvement of the participants in the new concept building which allowed their learning. The results of the research indicate the importance of problem solving as a teaching strategy, which can provide the students the building of their own knowledge.